Body composition of active persons with spinal cord injury and with poliomyelitis - Ribeiro, Sandra Maria Lima; Kehayias, Joseph; Silva, Regina Célia da; Tirapegui, Julio (Acta Fisiátrica, 2011)
This study sought to evaluate the body composition of subjects with active spinal cord injuries and polio. Method: Two groups of males and females, active, free-living, of similar ages and body mass index (BMI), were distributed according to the source of deficiency: SCI – low spinal cord injury (T5-T12) and P – survivors of poliomyelitis infection. Body composition was analyzed by DEXA (fat and lean mass); bioelectrical impedance by vector analysis (BIVA analysis; resistance and reactance). Participants of the same gender were compared according to the source of deficiency, and both groups had their values compared to a reference population, when available. Results: Mean vectors were assessed with Hotelling’s T2 test and compared by Mahalanobis distance (D). DEXA analysis pointed out the men of P group with higher absolute amount of lean mass, and consequently the higher body lean mass index; both groups presented lower values than a reference study. With regard to BIVA analysis, P men presented higher resistance than SCI men and, consequently, a lower phase angle. Conclusion: Considering body composition as an indirect indicator of nutritional status, the present study suggests that, even with both groups presenting lower values than a reference population, there is a possibility of an increased nutritional risk for polio individuals than SCI, and this risk seems to be higher in men than in women. Further investigation, adopting biochemical and dietetic markers, and a higher sample size, certainly could better explore and understand our results.